How Nutrients Orchestrate Lysosome Positioning. (March 2018) - Raiborg, Camilla
As part of a starvation response, lysosomes cluster perinuclearly. This facilitates fusion between lysosomes and autophagosomes and ensures activation of catabolic processes. When nutrients are abundant, lysosomes rather translocate to the cell periphery where they contribute to anabolic signaling. The mechanisms underlying nutrient-dependent lysosome positioning have been enigmatic. Now, several recent reports shed light on these mechanisms, and we are beginning to understand how the nutritional status can control and coordinate lysosome translocation pathways. Interestingly, several of the mechanisms that control lysosome positioning depend on membrane contact sites.